Zakat Core Principles (ZCP)-Based Good Amil Governance in Palembang City's Amil Zakat Institutions - Shalihah, Bunga Mar'atush (Center of Strategic Studies (PUSKAS) BAZNAS, 2026)
PurposeThe purpose of this study is to determine whether the zakat amil institutions in Palembang City have implemented PPZ 8—good governance of amil amil—in accordance with the governance standards established by BAZNAS in the Zakat Core Principles (ZCP). The muzakki who distribute their zakat to be delivered to the mustahiq who have been recorded and can be assured to meet the governance values that apply to zakat amil institutions in Palembang city will effectively respond to this study. Design/Methodology/ApproachThis study used an inductive approach and a descriptive qualitative research methodology. In-depth interviews with chosen informants, specifically the Zakat Collection Institutions (LAZ), were used for primary data collection. LazisMU, Dompet Dhuafa, and the Infaq Management Institution (LMI) were the three LAZs chosen. The management of each LAZ who were aware of the zakat collection institutions' governance structure served as the informants. This qualitative study's data analysis procedure was done iteratively, beginning with the first phases of data collection and continuing all the way through the writing stage. An orderly and systematic search through interview transcripts, field notes, and other materials collected from the field constitutes data analysis. FindingsAccording to the findings of this study, the amil's use of good management practices at the three zakat institutions under investigation has been very successful, despite the fact that two LAZ have failed to meet standards. It is hoped that future research will look into other LAZ with a larger number to better represent results at a higher level. Furthermore, the BAZNAS-established principles for zakat institutions must be updated. Research limitations/implicationsThis research only studied three LAZ that located in Palembang’s City as a sample, for further researcher to adding more LAZ to studied for the best result about implementation of Good Amil Governance in amil zakat institutions. Practical implicationsThe result about implementation of Good Amil Governance in LAZ could be practice to every level of amil zakat institution. However, the policy to Amil certification could held and taken by regional or local BAZNAS and informed to amil zakat institution belong to private or non-government. Social implicationsThis study impacted the social result as LAZ is the place for society to distribute their zakat, infaq and shadaqah to be shared to those in needs. To maintaining the society trust, every LAZ should apply the zakat core principles by BAZNAS and fulfilling the indicator of Good Amil Zakat criteria. Originality/valueThis study is using non-government amil zakat institutions such as LazisMu, Dompet Dhuafa and Lembaga Manajemen Infak (LMI) as a study samples with hope meets all of indicators for fulfilling Good Amil Governance conducted by BAZNAS.